2016
DOI: 10.1038/onc.2016.128
|View full text |Cite
|
Sign up to set email alerts
|

Type I interferons exert anti-tumor effect via reversing immunosuppression mediated by mesenchymal stromal cells

Abstract: Mesenchymal stromal cells (MSCs) are strongly immunosuppressive via producing nitric oxide (NO) and known to migrate into tumor sites to promote tumor growth, but the underlying mechanisms remain largely elusive. Here, we found that IFNα-secreting MSCs showed more dramatic inhibition effect on tumor progression than that of IFNα alone. Interestingly, IFNα-primed MSCs could also effectively suppress tumor growth. Mechanistically, we demonstrated that both IFNα and IFNβ (type I IFNs) reversed the immunosuppressi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

2
30
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 33 publications
(32 citation statements)
references
References 55 publications
2
30
0
Order By: Relevance
“…(22) sought to determine the mechanisms of the antitumor effects exerted by MSCs-producing IFNα. Using the B16 mouse melanoma model, they found that IFNα acts synergistically with MSCs against tumor proliferation (22).…”
mentioning
confidence: 99%
See 4 more Smart Citations
“…(22) sought to determine the mechanisms of the antitumor effects exerted by MSCs-producing IFNα. Using the B16 mouse melanoma model, they found that IFNα acts synergistically with MSCs against tumor proliferation (22).…”
mentioning
confidence: 99%
“…(22) sought to determine the mechanisms of the antitumor effects exerted by MSCs-producing IFNα. Using the B16 mouse melanoma model, they found that IFNα acts synergistically with MSCs against tumor proliferation (22). Remarkably, MSCs primed with IFNα for 24 hours prior to intramuscular co-injection with B16F0 melanoma cells in C57BL/6 mice suppressed tumor growth in vivo , whereas control MSCs slightly increased tumor growth (22).…”
mentioning
confidence: 99%
See 3 more Smart Citations